STATUS PEMANTAUAN KESEHATAN HUTAN YANG DIKELOLA OLEH KELOMPOK TANI HUTAN SHK LESTARI - Rahmat Safei; Yullia Indriani; Arief Darmawan; Hari Kaskoyo (Fakultas Kehutanan Universitas Jambi, 2019)
Data and information on forest health conditions can be obtained by periodically monitoring forest health. Regular forest health monitoring can support the achievement of sustainable forest management so as to guarantee the quantity and quality of forests. This study aims to obtain the value of the status of forest conditions that are managed by the Sustainable Community Forestry System (SHK) group. This study uses the Forest Health Monitoring (FHM) method with a sample measuring plot in the form of six FHM clusters. The results showed that the value of the status of the condition of the forests managed by the SHK Lestari group was in the bad criteria (clusters 1, 2, 3, and 6) and good (clusters 4 and 5). Thus, the status of forest conditions managed by the SHK Lestari group is on average bad. Keywords; Forest health monitoring, SHK Lestari, Status values